Developing and Maintaining Adaptable Radical Innovation Capability (Dynamic Capability) - Gabriel, R. E. (2016)
Radical product innovation capability as a type of dynamic capability has received much attention in recent time. This area of strategy has generated growing number of research on how it can be developed and kept sustainable. However past research fall short of extended the knowledge to capture the use adaptive capabilities that are interrelated. This dissertation presents a historical research for the literature on radical product innovation capability. It illustrates how the sustainability of a firm’s radical product innovation can be improved by extending this capability to include adaptive capabilities that function as a web. This adaptive capability is made up of components embedded in the radical product innovation capability such as: firm characteristics, senior leadership, organizational culture, product launch strategy and product performance. So far, research has focused on singular interactions between these factors. Conversely the question of how the interplay of these factors affects the adaptability of a firm’s radical product innovation capability previously remained unexplored. The research concludes by showing how the interplay among these components improves the fit of a firm’s radical product innovation capability to fast changing product market.